2023
DOI: 10.1021/acscatal.2c06289
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Aging of Rh/ZrO2–CeO2 Three-Way Catalysts under Dynamic Lean/Rich Perturbation Accelerates Deactivation via an Encapsulation Mechanism

Abstract: A Rh/ZrO 2 −CeO 2 (Rh/ZC) three-way catalyst was exposed to hightemperature exhaust gas mixtures fluctuating between stoichiometric (S), oxidizing (fuellean, L), and reducing (fuel-rich, R) compositions. The catalyst deactivation during thermal aging at 1000 °C for 40 h under a dynamic SLR cycle condition (S: 25 s, L: 2.5 s, and R: 2.5 s) was more severe than that under static conditions (S, L, or R). Chemisorption, transmission electron microscopy, and X-ray photoelectron spectroscopy showed that the total en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…Figure a compares the cumulative conversion efficiencies of each gas species in 20–200 s of the test period. As recently reported, the extent of catalyst deactivation is strongly dependent on the atmosphere of the engine aging (1000 °C, 40 h), which was in the following order: R < S ≈ L ≪ SLR. The extremely contrasting behavior between R and SLR correlated with a bar graph in Figure a, confirming the significant deactivation of SLR40 compared with that of R40.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure a compares the cumulative conversion efficiencies of each gas species in 20–200 s of the test period. As recently reported, the extent of catalyst deactivation is strongly dependent on the atmosphere of the engine aging (1000 °C, 40 h), which was in the following order: R < S ≈ L ≪ SLR. The extremely contrasting behavior between R and SLR correlated with a bar graph in Figure a, confirming the significant deactivation of SLR40 compared with that of R40.…”
Section: Resultsmentioning
confidence: 99%
“…We confirmed that the encapsulation of Rh nanoparticles under SLR aging was unlikely to happen on the γ-Al 2 O 3 support. 20 The migration of PGMs in TWCs has been reported by several research groups. 29,45−47 It depends not only on the types of PGM/support and their interactions but also on the temperature, gas atmosphere, and sintering stage.…”
Section: Possible Mechanism Of Deactivation Mitigationmentioning
confidence: 92%
See 3 more Smart Citations